From Zaragoza to Calabria: Lucio Marineo, Juan de Molina, Federico Rocca and the translation of an aragonese chronicle (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This paper analyzes the translation of the aragonese chronicle De Primis Aragoniae Regibus, written by the humanist Lucio Marineo, from the perspective of the editorial policy. The work of the sicilian writer was translated into spanish by Juan de Molina and its version into italian by Federico Rocca. The three of them within a historical and cultural context that tries to legitimize the political role of the nobility of aragonese origin.
Keywords: Humanism; Luico Marineo; Juan de Molina; Federico Rocca; chronicle; Aragon